Keynote Address on Preserving the Architecture of Historic Cities and Sacred Places - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed the importance of preserving culture, cities and architecture, and sacred sites. The international system has to be built on structure, on governance, on justice, on legal systems, on social systems, but it also has to be built on history and culture. You do not have to have a dollar sign on something for it to be valuable or for it to be essential. You cannot have an international financial architecture built on sand. He discussed the overwhelming issue of poverty, concentration of people in cities, the pressure on public services and public spaces, and the degradation that accompanies movements of people into cities.